2013
DOI: 10.1007/s11252-013-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Local and landscape drivers of arthropod abundance, richness, and trophic composition in urban habitats

Abstract: Urban green spaces, such as forest fragments, vacant lots, and community gardens, are increasingly highlighted as biodiversity refuges and are of growing interest to conservation. At the same time, the burgeoning urban garden movement partially seeks to ameliorate problems of food security. Arthropods link these two issues (conservation and food security) given their abundance, diversity, and role as providers of ecosystem services like pollination and pest control. Many previous studies of urban arthropods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 55 publications
(60 reference statements)
10
66
1
Order By: Relevance
“…Similar to Philpott et al (2014), we observed a negative effect of the amount of surrounding vegetation in a 100m-radius on ant abundance failing to our last hypothesis (H3). Some ants could have the ability to use impervious surface as habitats more than vegetated patches.…”
Section: A Contrasting Effect Of Surrounding Greening Index and Managsupporting
confidence: 63%
“…Similar to Philpott et al (2014), we observed a negative effect of the amount of surrounding vegetation in a 100m-radius on ant abundance failing to our last hypothesis (H3). Some ants could have the ability to use impervious surface as habitats more than vegetated patches.…”
Section: A Contrasting Effect Of Surrounding Greening Index and Managsupporting
confidence: 63%
“…Our family richness and morphospecies richness are similar to other spider studies that were performed in central California, or that had similar methods. In past non-California urban habitat studies that used pitfall traps, family richness averaged at 18 spider families and 64 morphospecies (Moorhead and Philpott 2013, Gardiner et al 2014, Philpott et al 2014). Fraser and Frankie (1986) compared spider communities in urban and natural habitats in Berkeley, CA, and found a total of 20 families and 75 morphospecies, with Gnaphosidae and Lycosidae dominant in pitfall traps for both habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…If local agriculture and food is to be truly beneficial, it is important that local agriculture conserves the biodiversity of the agro-ecosystem. Thus, it is the role of sustainable agriculture to contribute to the conservation of organisms that play important activities such as pollination and pest control (Philpott et al, 2014).…”
Section: Local Food and Sustainabilitymentioning
confidence: 99%